Slum urbanization in buenos aires province (2009)
The informal settlements question has a long history in Argentina and has been met by different public programs, the last of which took place thirty years ago and had limited and questionable results. The Slum and Informal Settlements Urbanization Program here studied, is part of an important national plan that has the aim to build 400.000 new houses around the country. Projects that are actually being executed in three neighbourhoods in Buenos Aires Metropolitan Area are studied, in a period comprehended between the Programs announcement (January 2005) and December 2006. The analysis is focalized on the local governments as protagonists of the Program implementation. The research results illustrate the existing links between political – institutional processes and spatial results, and the consequences for life quality of the involved population.